Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

An update on fermented plant-based dairy alternatives: Advances towards consumer acceptability and modern diets - Jonata M. Ueda; Virginia Fernández-Ruiz; Patricia Morales; Anabela Ferreira; Sandrina A. Heleno; Márcio Carocho (Food Research International, 2025)

The Role of SOS1 and HKT Transporters in Na+ Exclusion in Huckleberry Under Saline Conditions - Dekoum V. M. Assaha; Ahmad Mohammad M. Mekawy; Liyun Liu; Hirofumi Saneoka; Akihiro Ueda (Tropical Plant Biology, 2025)

Impact of the drying process and incorporation of natural preservatives on the viability of lactic acid bacteria in yogurts - Jonata M. Ueda; Patricia Morales; Márcio Carocho; Sandrina A. Heleno (Phytochemistry Letters, 2025)

Effects of amount of lactose in milk replacer on gastrointestinal function of dairy calves - R. Fukumori; T. Nakayama; M. Hirose; I. Norimura; K. Izumi; K. Shimada; H. Mineo; M.A. Steele; S. Gondaira; H. Higuchi; T. Watanabe; H. Ueda; et al. (Animal Feed Science and Technology, 2025)

Comparative analysis of physiological, enzymatic, and genetic responses revealed the differences in salt tolerance between two rice varieties at the seedling stage - Ahmad Mohammad M. Mekawy; Dekoum V.M. Assaha; Li Jiacheng; Akihiro Ueda (South African Journal of Botany, 2024)

Differential Physiological and Molecular Processes in the Root May Underlie Contrasting Salt Tolerance in Two Egyptian Rice Cultivars at the Seedling Stage - Ahmad Mohammad M. Mekawy; Dekoum V.M. Assaha; Jiacheng Li; Asmaa Yusuf; Doaa Mostafa; Mahmoud Ali Shoulkamy; Akihiro Ueda (Journal of Soil Science and Plant Nutrition, 2024)
This study aimed to compare various responses of two Egyptian rice accessions bred for high yields, Sakha108 and Giza177, to salt stress at the seedling stage. Twenty-eight-day-old seedlings of two cultivars were grown in a hydroponic medium under control conditions (no NaCl) and salt stress (75 mM NaCl) for 12 days. Growth (dry weight), Na + and K + concentrations, enzymatic and non-enzymatic antioxidants, malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and expression of Na + and K + transport-coding genes were recorded. Sakha108’s growth (18% rise from control) was significantly higher than Giza177’s. Both cultivars accumulated similar amounts of Na + in the leaves and sheaths, however, Sakha108 had higher Na + concentrations in the roots than Giza177 (13.3% higher). Root K + concentration dropped dramatically (~ 2-fold reduction) in Giza177 roots while remaining unchanged in Sakha108 roots. The concentrations of H 2 O 2 (root) and MDA (leaf and root) were higher in Giza177 than in Sakha108, although the difference was not statistically significant. Proline and total flavonoid (TF) contents in Sakha108 roots were greater than those in Giza177 roots. The expression of OsHKT1;5 and OsHKT2;1 genes declined in both cultivars, whereas expressions of OsSOS1 , OsNHX1 , and OsHAK7 were induced in Sakha108 but, except for OsHAK7 , were repressed in Giza177. Combined, these findings suggest that Sakha108 is more resistant to salt stress than Giza177 is, and that this variation in tolerance may have its origins in the root systems of the two cultivars. Thus, these adaptive traits in the root of Sakha 108 could be explored for engineering stress tolerance in susceptible but high-yielding rice cultivars.

Detrital zircon U–Pb ages and geochemistry of Devonian–Carboniferous sandstones and volcanic rocks of the Hida Gaien belt, Southwest Japan: Provenance reveals a Gondwanan lineage for the early Paleozoic tectonic evolution of proto-Japan - Keisuke Suzuki; Toshiyuki Kurihara; Teruki Sato; Hayato Ueda; Toshiro Takahashi; Simon A. Wilde; M. Satish-Kumar (Gondwana Research, 2023)

Fermented food/beverage and health: current perspectives - Alessandra Durazzo; Marcio Carocho; Sandrina A. Heleno; Mariana C. Pedrosa; Jonata M. Ueda; Lillian Barros; Eliana B. Souto; Antonello Santini; Massimo Lucarini (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Regulation of Na+ and K+ Transport and Oxidative Stress Mitigation Reveal Differential Salt Tolerance of Two Egyptian Maize (Zea mays L.) Hybrids at the Seedling Stage - Mosa Sayed Rizk; Ahmad M. M. Mekawy; Dekoum V. M. Assaha; Sumana Chuamnakthong; Nagwa Ebrahim Shalaby; Akihiro Ueda (Journal of Plant Growth Regulation, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Correction to: Differential Salt Sensitivity of Two Flax Cultivars Coincides with Differential Sodium Accumulation, Biosynthesis of Osmolytes and Antioxidant Enzyme Activities - Ahmad Mohammad M. Mekawy; Dekoum V. M. Assaha; Akihiro Ueda (Journal of Plant Growth Regulation, 2020)

Differential Salt Sensitivity of Two Flax Cultivars Coincides with Differential Sodium Accumulation, Biosynthesis of Osmolytes and Antioxidant Enzyme Activities - Ahmad Mohammad M. Mekawy; Dekoum V. M. Assaha; Akihiro Ueda (Journal of Plant Growth Regulation, 2020)

Dietary nitrate does not acutely enhance skeletal muscle blood flow and vasodilation in the lower limbs of older adults during single-limb exercise - William E. Hughes; Nicholas T. Kruse; Kenichi Ueda; Andrew J. Feider; Satoshi Hanada; Joshua M. Bock; Darren P. Casey (European Journal of Applied Physiology, 2020)

Constitutive overexpression of rice metallothionein-like gene OsMT-3a enhances growth and tolerance of Arabidopsis plants to a combination of various abiotic stresses - Ahmad Mohammad M. Mekawy; Dekoum V. M. Assaha; Akihiro Ueda (Journal of Plant Research, 2020)

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Effects of Transcranial Direct Current Stimulation of the Posterior Parietal Cortex on the Control of Visual Attention - Y. Hirakawa; K. Takeda; S. Tanabe; S. Koyama; T. Ueda; K Morishima; M. Iwai; S. Kuno; I. Motoya; H. Sakurai; Y. Kanada (Neurophysiology, 2019)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Enhanced loading regimen of teicoplanin is necessary to achieve therapeutic pharmacokinetics levels for the improvement of clinical outcomes in patients with renal dysfunction - T. Ueda; Y. Takesue; K. Nakajima; K. Ichiki; A. Doita; Y. Wada; T. Tsuchida; Y. Takahashi; M. Ishihara; H. Ikeuchi; M. Uchino; T. Kimura (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Biological index of environmental lead pollution: accumulation of lead in liver and kidney in mice - T. Takano; Y. Okutomi; M. Mochizuki; Y. Ochiai; F. Yamada; M. Mori; F. Ueda (Environmental Monitoring and Assessment, 2015)

Nitric oxide is not a negative regulator of metamorphic induction in the abalone Haliotis asinina - Nobuo Ueda; Sandie M. Degnan (Frontiers in Marine Science, 2014)

TLC screening of thraustochytrid strains for squalene production - Atsushi Nakazawa; Yume Kokubun; Hiroshi Matsuura; Natsuki Yonezawa; Ryoji Kose; Masaki Yoshida; Yuuhiko Tanabe; Emi Kusuda; Duong Van Thang; Mayumi Ueda; Daiske Honda; Aparat Mahakhant; et al. (Journal of Applied Phycology, 2014)

Characterization of a new anulavirus isolated from Amazon lily plants - S. Fuji; M. Kikuchi; S. Ueda; T. Toda; H. Furuya; F. Fukumoto; K. Hanada (Archives of Virology, 2013)

Distribution of prolactin receptors suggests an intraductal role for prolactin in the mouse and human mammary gland, a finding supported by analysis of signaling in polarized monolayer cultures - Eric K. Ueda; KuangTzu Huang; Virginia Nguyen; Marco Ferreira; Saudade Andre; Ameae M. Walker (Cell and Tissue Research, 2011)

Labidocera boxshalli sp. nov., a new calanoid copepod (Crustacea; Pontellidae) from the Red Sea - Mohsen M. El-Sherbiny; Hiroshi Ueda (Organisms Diversity & Evolution, 2010)

Unique grouping of the Far East Asian begomovirus complex based on sequence analyses of the DNA-A genome and associated DNAβ satellite molecules isolated from tomato, honeysuckle and Eupatorium plants in Japan - S. Ueda; M. Onuki; K. Hanada; Y. Takanami (Archives of Virology, 2008)

Collagen type I matrix affects molecular and cellular behavior of purified porcine dental follicle cells - S. Tsuchiya; M. J. Honda; Y. Shinohara; M. Saito; M. Ueda (Cell and Tissue Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Distribution and characteristics of molecular size fractions of freshwater-dissolved organic matter in watershed environments: its implication to degradation - Takahito Yoshioka; Khan M. G. Mostofa; Eiichi Konohira; Eiichiro Tanoue; Kazuhide Hayakawa; Mikio Takahashi; Shingo Ueda; Masanori Katsuyama; Tamara Khodzher; Nadezhda Bashenkhaeva; Irina Korovyakova; Larisa Sorokovikova; et al. (Limnology, 2007)

Relationship between eyed‐egg percentage and levels of cortisol and thyroid hormone in masu salmon Oncorhynchus masou - M. Mingist; T. Kitani; N. Koide; H. Ueda (Journal of Fish Biology, 2007)
A possible cause of the low eyed‐egg percentage that afflicts pond‐reared masu salmon Oncorhynchus masou at a fish hatchery (Kumaishi Fish Hatchery, Hokkaido, Japan) was investigated. Serum cortisol levels of masu salmon during the spawning period were compared between individuals from Kumaishi and those from another station (Mori). Cortisol, thyroxine (T 4 ) and triiodothyronine (T 3 ) hormones were also measured in eyed eggs and their levels were compared to the eyed‐egg percentage. Serum cortisol levels were significantly higher at Kumaishi than at Mori in May and July of the breeding season. At the Kumaishi station, there was a linear positive relationship between serum cortisol and fertilized‐egg cortisol levels of female masu salmon. As cortisol levels in both ovulating females and eyed eggs increased, the eyed‐egg percentage decreased, indicating a highly significant negative relationship between cortisol levels and eyed‐egg percentage. In contrast, as T 3 and T 4 levels in eyed eggs increased, the eyed‐egg percentage increased. The strong positive correlation between high cortisol levels in serum and in eyed eggs at Kumaishi indicates that the frequently higher cortisol levels may have caused the lowering of the eyed‐egg percentage.

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

Molecular mechanisms involved in anti-inflammatory effects of proton pump inhibitors - O. Handa; N. Yoshida; N. Fujita; Y. Tanaka; M. Ueda; T. Takagi; S. Kokura; Y. Naito; T. Okanoue; T. Yoshikawa (Inflammation Research, 2006)

Complete nucleotide sequence of the genomic RNA of an Amami-O-shima strain of East Asian Passiflora potyvirus - H. Iwai; R. Terahara; Y. Yamashita; S. Ueda; M. Nakamura (Archives of Virology, 2006)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Elimination of chrysanthemum stunt viroid from an infected chrysanthemum cultivar by shoot regeneration from a leaf primordium-free shoot apical meristem dome attached to a root tip - M. Hosokawa; A. Otake; K. Ohishi; E. Ueda; T. Hayashi; S. Yazawa (Plant Cell Reports, 2004)

Delimitation of the chromosomal region for a quantitative trait locus, qUVR-10, conferring resistance to ultraviolet-B radiation in rice (Oryza sativa L.) - T. Ueda; T. Sato; H. Numa; M. Yano (Theoretical and Applied Genetics, 2004)

Comparative analyses of serum vitellogenin levels in male and female Reeves' pond turtles ( Chinemys reevesii ) by an immunological assay - Y. Ueda; H. Hoshi; T. Uemura; Y. Kamata; N. Tada; M. Saka (Journal of Comparative Physiology B, 2004)

Mapping of quantitative trait loci associated with ultraviolet-B resistance in rice (Oryza sativa L.) - T. Sato; T. Ueda; Y. Fukuta; T. Kumagai; M. Yano (Theoretical and Applied Genetics, 2003)

Changes in neurosteroid biosynthesis during sexual maturation of lacustrine sockeye salmon - S. Matsumoto; H. Yamada; M. Iwata; S. Adachi; K. Yamauchi; H. Ueda (Fish Physiology and Biochemistry, 2003)

Changes in GnRH levels in the brain and pituitary gland during migrations of sockeye salmon and chum salmon - T. Kitani; S. Matsumoto; H. Yamada; M. Amano; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2003)

Detection of Japanese yam mosaic virus by RT-LAMP - S. Fukuta; T. Iida; Y. Mizukami; A. Ishida; J. Ueda; M. Kanbe; Y. Ishimoto (Archives of Virology, 2003)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Seasonal changes of hormones and muscle enzymes in adult lacustrine masu (Oncorhynchus masou) and sockeye salmon (O. nerka) - J.B.K. Leonard; M. Iwata; H. Ueda (Fish Physiology and Biochemistry, 2001)

Nephrotoxicity of D -propargylglycine in mice - R. Konno; M. Ikeda; K. Yamaguchi; Y. Ueda; A. Niwa (Archives of Toxicology, 2000)

Microtubule-dependent migration of the cell nucleus toward a future leading edge in amoebae ofPhysarum polycephalum - M. Ueda; T. Kuroiwa; S. Matsunaga; S. Ogihara (Protoplasma, 2000)

Polychlorinated Dibenzo- p -Dioxins (PCDDs), Dibenzofurans (PCDFs), Biphenyls (PCBs), and Organochlorine Pesticides in Yellow-Blotched Map Turtle from the Pascagoula River Basin, Mississippi, USA - K. Kannan; M. Ueda; J. A. Shelby; M. T. Mendonca; M. Kawano; M. Matsuda; T. Wakimoto; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2000)

Interannual, seasonal, local and body size variations in reproduction of the prawn Penaeus ( Marsupenaeus ) japonicus (Crustacea: Decapoda: Penaeidae) in the Ariake Sea and Tachibana Bay, Japan - M. Minagawa; S. Yasumoto; T. Ariyoshi; T. Umemoto; T. Ueda (Marine Biology, 2000)

Human cytotoxic T-lymphocyte responses specific for peptides of the wild-type Wilms' tumor gene ( WT1 ) product - Y. Oka; O. A. Elisseeva; A. Tsuboi; H. Ogawa; H. Tamaki; H. Li; Y. Oji; E. H. Kim; T. Soma; M. Asada; K. Ueda; E. Maruya; et al. (Immunogenetics, 2000)

Allelic diversity at class II DRB1 and DQB loci of the pig MHC ( SLA ) - T. Hosokawa Kanai; Y. Tanioka; M. Tanigawa; Y. Matsumoto; S. Ueda; T. Onodera; Y. Matsumoto (Immunogenetics, 1999)

Analysis of 5′-upstream non-coding region of FI-carboxymethyl cellulase gene from Aspergillus aculeatus - T. Ooi; K. Morotomi; S. Kinoshita; J. Honda; S. Ueda; M. Arai (Biotechnology Letters, 1999)

Phylogenetic relationships of the enigmatic fern families Hymenophyllopsidaceae and Lophosoriaceae: Evidence fromrbcL nucleotide sequences - Paul G. Wolf; Sedonia D. Sipes; Martha R. White; Michael L. Martines; Kathleen M. Pryer; Alan R. Smith; Kunihiko Ueda (Plant Systematics and Evolution, 1999)

Hydrothermal carbonates in altered wall rocks at the Uwamuki Kuroko deposits, Japan - N. Shikazono; M. Hoshino; M. Utada; M. Nakata; A. Ueda (Mineralium Deposita, 1998)

Slight difference in primary amino acid sequence of p17 matrix protein of HIV-1 exerts profound influence on its antigenicity - K. Taniguchi; H. Tsuchie; S. Kageyama; M. Iwasaki; T. Takagi; F. Sasao; S. Ueda; T. Kurimura (Archives of Virology, 1998)

Genomic organization and chromosomal localization of the human casein gene family - Y. Fujiwara; M. Miwa; M. Nogami; K. Okumura; T. Nobori; T. Suzuki; M. Ueda (Human Genetics, 1997)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

Characterization of a temperature-sensitive mutant in the RNA polymerase PB2 subunit gene of influenza A/WSN/33 virus - K. Yamanaka; N. Ogasawara; M. Ueda; H. Yoshikawa; A. Ishihama; K. Nagata (Archives of Virology, 1990)

Genetic variants of protease inhibitors against fungal protease and ?-chymotrypsin from hemolymph of the silkworm, Bombyx mori - M. Eguchi; K. Ueda; M. Yamashita (Biochemical Genetics, 1984)

Temperature-sensitive virion transcriptase activity in mutants of WSN influenza virus - S. L. Mowshowitz; M. Ueda (Archives of Virology, 1976)

Structure-biodegradability relationships in pyrethroid insecticides - John E. Casida; Kenzo Ueda; Loretta C. Gaughan; Lien T. Jao; David M. Soderlund (Archives of Environmental Contamination and Toxicology, 1975)

Temperature-sensitive mutants of influenza virus - M. Ueda (Archives of Virology, 1972)

The effect of actinomycin D on the synthesis of influenza virus-specific RNA - A. Sugiura; M. Ueda; C. Enomoto (Archives of Virology, 1969)